Radioactive: Analysis of the potential of the film as a material for Scientific Dissemination (Research, Society and Development, 2022)
Movies have been used as a didactic tool to present scientific knowledge in the classroom. The movie "Radioactive" released in 2019 portrays aspects of the life of scientist Marie Curie and her scientific journey with her husband Pierre. In this sense, this work sought to identify the possible contributions of the film as a tool for scientific dissemination and present its educational potential for use in the classroom. Thus, we tried to understand in the scenes of the film aspects related to the context of women in science, how the film approaches the subject of radioactivity and identify aspects that portray the scientific activity; for this, we used the Textual Discourse Analysis for data treatment. It is concluded that the use of cinematographic works generates public involvement, and the film presents significant potential to be used as a material for scientific dissemination bringing contributions to both the teaching and learning process and the democratization of knowledge.